RANCANGAN BANGUN SISTEM BULLWHIP EFFECT PADA PT. MITRA ASAHAN SELALU JAYA KECAMATAN SIMPANG EMPAT MENGGUNAKAN SUPPLY CHAIN MANAGEMENT (SCM) - Nasution, Irmawati; Anggreani, Dewi; Santoso, Santoso (STKIP PGRI Tulungagung, 2024)
In distributing 3kg LPG to the public, PT Mitra Asahan Always Jaya has 51 permanent base partners with various contracts and different quota amounts. Currently subsidized 3kg LPG agents are not permitted to sell subsidized 3kg LPG directly to consumers. With a working area with a very large number of requests from each agent, this is due to the large number of base partners having food trading businesses, not to mention having to meet the demand for household gas, micro businesses and retailers. so that the distribution chain at PT Mitra Asahan Always Jaya, Simpang Empat District, has an erratic demand, the gas distribution system to bases is uneven and not fulfilled due to the gas order management data not being well structured, bases are unable to order gas faster than usual. because the gas quota stock at PT Mitra Asahan Always Jaya, Simpang Empat District, is insufficient, this is due to the lack of management analysis in the gas supply at the base. Many bases have made gas orders, but officers in the field do not communicate to management about the gas requirements actually needed by the base, so that distributors or bases sometimes have to bear losses due to running out of stock